Potential antibacterial effects and transcriptomic analysis of a novel reversible photoacid-based crystalline coordination polymer - Zheng, Chenhua; Zheng, Yaying; Wu, Binjie; Zheng, Yuyan; Yu, Shuye; Qiu, Rui; Chen, Wanling; Chen, Xin; Li, Longze; Liao, Jianzhen; Hu, Fen (Frontiers in Microbiology, 2025)
IntroductionWith the increasing prevalence of antibiotic resistance, the development of novel antibacterial materials is crucial to combat clinically relevant pathogens. This study comprehensively investigated the antibacterial properties and underlying mechanisms of a novel reversible photoacid-based crystalline material.MethodsThe antibacterial efficacy of the material was evaluated against six clinically relevant pathogenic bacteria, including multidrug-resistant strains. The inhibition rates were determined, and scanning electron microscopy (SEM) was used to observe the effects on cell surface integrity. Transcriptomic analysis was conducted to elucidate the underlying antibacterial mechanisms.ResultsThe material exhibited broad-spectrum antibacterial activity, with higher sensitivity toward Gram-negative bacteria. Blue light irradiation significantly enhanced its antibacterial efficacy. SEM revealed that the material disrupted cell membrane integrity, leading to cell death. Transcriptomic analysis showed that the material inhibited bacterial protein synthesis, disrupted cell membrane protein synthesis, and downregulated oxidative stress-related genes, causing ROS accumulation and inhibiting cell growth.DiscussionThese findings provide a theoretical basis for the potential clinical application of this material as a new antibacterial agent. The material’s ability to enhance antibacterial efficacy through light irradiation and its broad-spectrum activity suggest it could be a valuable tool in combating antibiotic-resistant pathogens. Future research should focus on further exploring the antibacterial mechanisms and evaluating the material’s safety and efficacy in clinical settings.